Model'nye harakteristiki tehniko-takticheskojpodgotovlennosti borcov vysokoj kvalifikaciigreko-rimskogo stilja razlichnyh vesovyh kategorij - Tropin, Y.; Korobeynikov, G.; Shatskikh, V.; Korobeynikova, L.; Vorontsov, A. (Science in Olympic Sport, 2019)
Objective. On the basis of the analysis of the competitive activity of highly skilled athletes to make model characteristics of technico-tactical fitness of Greco-Roman wrestlers of different weight categories. Methods. Theoretical analysis and generalization of data of special literature, analysis of protocols and videos of final and semi-final matches of highly skilled Greco-Roman wrestlers at the European Championship and 2018 World Championship, methods of mathematical statistics. By means of expert estimate, 99 videos of competitive bouts have been analyzed. Results. On the basis of the analysis of modern competitive activities of highly skilled wrestlers, 10 main technical actions that are most often used have been identified: rolling sideways, rear and reversed belt throwings, counter-holds in "referee`s" position and in stance, taking-down on the mat, backward bending throwing and hip throwing, take-down, pushing beyond the mat. It has been established that all groups of wrestlers in the "referee`s" position mostly execute rolling sideways with the most successful being the athletes of the average weight category - 41 %, light - 39 % and heavy weight category - 30 %. Analysis of the content of holds in stance suggests that the percentage contribution of take-downs in the total number of technical actions varies slightly for all styles of fights and constitutes in the wrestlers of the light weight category 14%, those of the average - 10 % and those of heavy - 16 %. Conclusion. The data obtained on the basis of theoretical knowledge and supported by practical indices as a result of the analysis of the fights between the winners of the final and semi-final matches at the major international competitions in 2018 (World Championship and European Championship), allowed to develop model characteristics of technical and tactical fitness for athletes of different weight categories, which can be used during the planning and management of the training process.